Room-temperature solution-processed and metal oxide-free nano-composite for the flexible transparent bottom electrode of perovskite solar cells. Issue 11 (29th February 2016) - Lu, Haifei; Sun, Jingsong; Zhang, Hong; Lu, Shunmian; Choy, Wallace C. H.
Abstract : A room-temperature solution-processed and metal oxide free nano-composite of metal nano-network and graphene oxide has been demonstrated as the flexible transparent bottom electrode of perovskite solar cell. Abstract : The exploration of low-temperature and solution-processed charge transporting and collecting layers can promote the development of low-cost and large-scale perovskite solar cells (PVSCs) through an all solution process. Here, we propose a room-temperature solution-processed and metal oxide-free nano-composite composed of a silver nano-network and graphene oxide (GO) flawless film for the transparent bottom electrode of a PVSC. Our experimental results show that the amount of GO flakes play a critical role in forming the flawless anti-corrosive barrier in the silver nano-network through a self-assembly approach under ambient atmosphere, which can effectively prevent the penetration of liquid or gaseous halides and their corrosion against the silver nano-network underneath. Importantly, we simultaneously achieve good work function alignment and surface wetting properties for a practical bottom electrode by controlling the degree of reduction of GO flakes. Finally, flexible PVSC adopting the room-temperature and solution-processed nano-composite as the flexible transparent bottom electrode has been demonstrated on a polyethylene terephthalate (PET) substrate. As a consequence, the demonstration of our room-temperature solution-processed and metal oxide-free flexible transparent bottom electrode will contribute to the emerging large-area flexible PVSC technologies.